Liposomal delivery of gene therapy for ovarian cancer: a systematic review - Son, Jin S.; Chow, Ryan; Kim, Helena; Lieu, Toney; Xiao, Maria; Kim, Sunny; Matuszewska, Kathy; Pereira, Madison; Nguyen, David L.; Petrik, Jim (Université d'Ottawa | University of Ottawa, 2023)
Abstract Objective To systematically identify and narratively synthesize the evidence surrounding liposomal delivery of gene therapy and the outcome for ovarian cancer. Methods An electronic database search of the Embase, MEDLINE and Web of Science from inception until July 7, 2023, was conducted to identify primary studies that investigated the effect of liposomal delivery of gene therapy on ovarian cancer outcomes. Retrieved studies were assessed against the eligibility criteria for inclusion. Results The search yielded 564 studies, of which 75 met the inclusion criteria. Four major types of liposomes were identified: cationic, neutral, polymer-coated, and ligand-targeted liposomes. The liposome with the most evidence involved cationic liposomes which are characterized by their positively charged phospholipids (n = 37, 49.3%). Similarly, those with neutrally charged phospholipids, such as 1,2-dioleoyl-sn-glycero-3-phosphatidylcholine, were highly researched as well (n = 25, 33.3%). Eight areas of gene therapy research were identified, evaluating either target proteins/transcripts or molecular pathways: microRNAs, ephrin type-A receptor 2 (EphA2), interleukins, mitogen-activated protein kinase (MAPK), human-telomerase reverse transcriptase/E1A (hTERT/EA1), suicide gene, p53, and multidrug resistance mutation 1 (MDR1). Conclusion Liposomal delivery of gene therapy for ovarian cancer shows promise in many in vivo studies. Emerging polymer-coated and ligand-targeted liposomes have been gaining interest as they have been shown to have more stability and specificity. We found that gene therapy involving microRNAs was the most frequently studied. Overall, liposomal genetic therapy has been shown to reduce tumor size and weight and improve survivability. More research involving the delivery and targets of gene therapy for ovarian cancer may be a promising avenue to improve patient outcomes.